2000
DOI: 10.1046/j.1469-8137.2000.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The trans‐tissue pathway and chemical fate of 14C photoassimilate in carrot taproot

Abstract: Axial and radial transport and the accumulation of photoassimilates in carrot taproot were studied using "%C labelling and autoradiography. Axial transport of the "%C labelled assimilates inside the taproot was rapid and occurred mainly in the young phloem found in rows radiating from the cambium. The radial transport of the assimilate inward (to cambium, xylem zone and pith) and outward (to phloem zone and periderm) from the conducting phloem was an order of magnitude slower than the longitudinal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies in carrot taproots have shown that radial movement of 14 C‐assimilate from the active phloem zone was more rapid in the centrifugal direction (i.e., across the phloem region) than in the centripetal one (across the cambium into xylem tissue); this highlights the role of cambium as a barrier for the radial movement of the assimilates into the xylem (Caplin 1973, Korolev et al 2000a). Thus, the increased growth and carbon deposition in the phloem parenchymatic zone at 12°C may be the consequence of both increased assimilate availability and the distinctive transport properties of assimilates within the carrot taproot.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in carrot taproots have shown that radial movement of 14 C‐assimilate from the active phloem zone was more rapid in the centrifugal direction (i.e., across the phloem region) than in the centripetal one (across the cambium into xylem tissue); this highlights the role of cambium as a barrier for the radial movement of the assimilates into the xylem (Caplin 1973, Korolev et al 2000a). Thus, the increased growth and carbon deposition in the phloem parenchymatic zone at 12°C may be the consequence of both increased assimilate availability and the distinctive transport properties of assimilates within the carrot taproot.…”
Section: Discussionmentioning
confidence: 97%
“…The intensively dividing cambial cells form an important sink (Korolev et al, 2000; Sauter, 2000) for nutrients transported from xylem and phloem regions, preferentially via the rays (Sauter and Kloth, 1986; van Bel, 1990; Korolev et al, 2000; Chaffey and Barlow, 2001). Radial cell‐to‐cell transport in rays may proceed via two different routes: symplasmically (van Bel, 1990; Korolev et al, 2000) or apoplasmically (van der Schoot and van Bel, 1989; Kitin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The intensively dividing cambial cells form an important sink (Korolev et al, 2000; Sauter, 2000) for nutrients transported from xylem and phloem regions, preferentially via the rays (Sauter and Kloth, 1986; van Bel, 1990; Korolev et al, 2000; Chaffey and Barlow, 2001). Radial cell‐to‐cell transport in rays may proceed via two different routes: symplasmically (van Bel, 1990; Korolev et al, 2000) or apoplasmically (van der Schoot and van Bel, 1989; Kitin et al, 2009). Abundant plasmodesmata in the tangential walls of ray cells (Farrar, 1995; Fuchs et al, 2010b), the radial arrangement of cytoskeleton elements in xylem and phloem rays (Chaffey and Barlow, 2001), the translocation of 14 C‐labeled assimilates in carrot taproot (Korolev et al, 2000), and the high radial flux rates of sugars through the ray cell tangential area (Sauter and Kloth, 1986; Sauter, 2000) support a symplasmic route of radial transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations